Simultaneous measurement of macro‐ and microvascular blood flow and oxygen saturation for quantification of muscle oxygen consumption. Issue 2 (11th May 2017) - Englund, Erin K.; Rodgers, Zachary B.; Langham, Michael C.; Mohler, Emile R.; Floyd, Thomas F.; Wehrli, Felix W.
Abstract : Purpose: To investigate the relationship between blood flow and oxygen consumption in skeletal muscle, a technique called "Velocity and Perfusion, Intravascular Venous Oxygen saturation and T 2 * " ( v PIVOT) is presented. v PIVOT allows the quantification of feeding artery blood flow velocity, perfusion, draining vein oxygen saturation, and muscle T 2 *, all at 4‐s temporal resolution. Together, the measurement of blood flow and oxygen extraction can yield muscle oxygen consumption ( V ˙ O 2 ) via the Fick principle. Methods: In five subjects, v PIVOT‐derived results were compared with those obtained from stand‐alone sequences during separate ischemia‐reperfusion paradigms to investigate the presence of measurement bias. Subsequently, in 10 subjects, v PIVOT was applied to assess muscle hemodynamics and V ˙ O 2 following a bout of dynamic plantar flexion contractions. Results: From the ischemia‐reperfusion paradigm, no significant differences were observed between data from v PIVOT and comparison sequences. After exercise, the macrovascular flow response reached a maximum 8 ± 3 s after relaxation; however, perfusion in the gastrocnemius muscle continued to rise for 101 ± 53 s. Peak V ˙ O 2 calculated based on mass‐normalized arterial blood flow or perfusion was 15.2 ± 6.7 mL O2 /min/100 g or 6.0 ± 1.9 mL O2 /min/100 g, respectively. Conclusions: v PIVOT is a new method to measure blood flow and oxygen saturation, and therefore to quantify muscle oxygen consumption. Magn Reson Med 79:846–855, 2018. © 2017 International Society for Magnetic Resonance in Medicine.